Front Cover: Advanced Engineering Materials 1∕2015. Issue 1 (January 2015) - Unknown
<x xml:space="preserve">Abstract</x> Titanium dioxide macroscopic fibers have been generated through a semiindustrial continuous process. This synthetic path allows generating several hyndred meters of fibers at once, while final fibers can be rolled continuously. When empoyed for air purification, using acetone as an organic pollutant, these fibers showed outstanding photocatalytic properties (degradation and mineralization) similar to a commercial product (Quartzel ®). Further details can be found in the article by Rénal Backov and co‐worker on page 37. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>